Listeria monocytogenes isolates from Cornu aspersum snails: Whole genome-based characterization and host-pathogen interactions in a snail infection model. Issue 123 (April 2022) - Kotzamanidis, Charalampos; Malousi, Andigoni; Dushku, Esmeralda; Dobly, Alexandre; De Keersmaecker, Sigrid C.J.; Roosens, Nancy H.; Karathodorou, Argyro; Staikou, Alexandra; Zdragas, Antonios; Yiangou, Minas
Abstract: Even though Listeria monocytogenes is an extensive-studied foodborne pathogen, genome analysis of isolates from snails that may represent a reservoir of L . monocytogenes are still scarce. Here, we use whole-genome sequencing (WGS) to assess the genomic diversity of hypervirulent, virulent and non-virulent phenotypes of 15 L. monocytogenes isolated from snails to unveil their survival, virulence, and host-pathogen mechanisms of interactions in a snail infection model. Most of isolates (66.7%) were characterized as multidrug resistant (MDR) and belonged to clonal complexes (CCs) which are strongly associated with cases of human infection. All isolates contained intact genes associated with invasion and infection while hypervirulent isolates are adapted to host environment, possessing genes which are involved in teichoic acid biosynthesis, peptidoglycan modification and biofilm formation, correlating with their tolerance to haemolymph plasma phenotype and biofilm formation ability. A snail infection model showed that hypervirulent isolates triggered programmed host cell death pathway by increasing up to 30% the circulating apoptotic hemocytes in combination with induced nitrate production and reactive oxygen species (ROS) generation in snails' haemolymph. In contrast, the administration of the non-virulent strain which possesses a truncated mog R gene that regulates flagellar motility gene expression led only to an increase of necrotic non-apoptotic cells. Overall, this study provides significant insights into the genetic diversity of L. monocytogenes from snails, the genomic features of them linked to their hypervirulent/non-virulent phenotype, and the mechanisms of host-pathogen interactions. Highlights: L. monocytogenes hypervirulent strains are adapted to host environment. Hypervirulent isolates trigger programmed host cell death pathway. L. monocytogenes non-virulent strains increase necrotic non-apoptotic cells. Truncated mog R gene in L. monocytogenes results in an increase of necrotic cells. Snail infection model is suitable to assess the L. monocytogenes virulence potential.